The comparison of wavelet and empirical mode decomposition method in prediction of sleep stages from EEG signals [EEG işaretlerinden uyku seviyesinin kestiriminde dalgacik ve görgül kip ayrişim yöntemlerinin karşilaştirilmasi] - Polat H.; Akin M.; Özerdem M.S. (Institute of Electrical and Electronics Engineers Inc., 2017)
The aim of this study was to detect sleep stages of human by using EEG signals. In accordance with this purpose, discrete wavelet transforms (DWT) and empirical mode decomposition (EMD) were separately used for feature extraction. Subcomponents of EEG signals obtained by the two methods were assumed as feature vectors. Statistical parameters were used to reduce dimension of feature vectors. The same statistical parameters were used to compare performance of methods related to DWT and EMD. K nearest neighborhood (kNN) algorithm was used in classification final feature vectors that obtained EEG segments related to different sleep stages. The classification accuracies for feature vectors based on DWT and EMD were obtained as 100% and 88.13%, respectively. © 2017 IEEE.
2017 International Artificial Intelligence and Data Processing Symposium, IDAP 2017 -- 16 September 2017 through 17 September 2017 -- -- 115012
Keywords: Classification; Discrete wavelet transform; EEG; Empirical mode decomposition